METHODOLOGY FOR MEASURING THE LOGISTICAL POTENTIAL OF AN INDUSTRIAL ENTERPRISE - VYSHNIUK, Sergii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates the relevance of improving methodological approaches to measuring the logistics potential of an industrial enterprise in the context of increasing supply chain complexity, digital transformation, market turbulence, and heightened uncertainty of the external environment. Logistics potential is interpreted as an integrated systemic characteristic of an enterprise’s ability to form, coordinate, and develop material, information, and financial flows in accordance with strategic objectives and changing operating conditions. Unlike traditional approaches that focus mainly on the availability of logistics resources, the proposed concept emphasizes the quality of their interaction, management efficiency, and the synergistic effects arising from the coordinated functioning of logistics subsystems. The study systematizes existing scientific approaches to defining logistics potential and identifies key structural components, including material and technical, production and distribution, information and digital, human resources, organizational, and managerial subsystems. An improved methodology for measuring the logistics potential of an industrial enterprise is proposed, based on a combination of quantitative and qualitative indicators and the introduction of a logistics synergy coefficient. This coefficient reflects the degree of coherence and mutual reinforcement among logistics subsystems and allows capturing non-linear effects that cannot be identified through partial indicators alone. The practical significance of the proposed approach lies in its applicability for diagnosing the current state of an enterprise’s logistics system, identifying internal reserves for improvement, and substantiating strategic decisions regarding logistics development. The use of the integral indicator enables enterprises to enhance adaptability, reduce logistics costs, increase resilience to disruptions, and strengthen competitive positions in both domestic and international markets.